Uniform continuity in definable groups (2018)
"The aim of the thesis is try to give a notion of uniform continuity compatible with the definable sets of a definable group. To do this we propose the notion of product sigma-continuous function and we show that, provided that G is enough saturated, the set of product sigma-continuous function is well behaved (it is a Banach space, for example)."--Tomado del Formato de Documento de Grado.